1989
DOI: 10.1007/bf00229063
|View full text |Cite
|
Sign up to set email alerts
|

The mediastinum of the bovine testis

Abstract: The bovine testis has a central mediastinum consisting of longitudinally oriented rete channels and spacious lymph vessels, embedded in the mediastinal stroma. The latter represents a contractile-elastic unit and is composed of myofibroblasts, collagen bundles and accumulations of elastin, connecting the myofibroblasts. The dimension of the mediastinum varies in cross sections at different levels between 3.5 and 31.8 mm2. In one cross section approximately 30 rete channels and approximately 30 openings of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In the lamina propria of the seminiferous tubules, contractile cells have been found in many mammalian species such as the rat, mouse, hamster, rabbit, cat, sheep, cattle, pig and human (Roosen-Runge 1951;Ross and Long 1966;Ross 1967;Böck et al 1972;Bressler and Ross 1972;Bustos-Obregón and Holstein 1973;De Kretser et al 1975;Hargrove et al 1977;Wrobel et al 1979;Maekawa et al 1996). Similar cells surround the channels of the rete testis (Roosen-Runge and Holstein 1978;Hees et al 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the lamina propria of the seminiferous tubules, contractile cells have been found in many mammalian species such as the rat, mouse, hamster, rabbit, cat, sheep, cattle, pig and human (Roosen-Runge 1951;Ross and Long 1966;Ross 1967;Böck et al 1972;Bressler and Ross 1972;Bustos-Obregón and Holstein 1973;De Kretser et al 1975;Hargrove et al 1977;Wrobel et al 1979;Maekawa et al 1996). Similar cells surround the channels of the rete testis (Roosen-Runge and Holstein 1978;Hees et al 1989).…”
mentioning
confidence: 99%
“…Maekawa et al 1996;Tripiciano et al 1999;Romano et al 2005, and references therein), although they seem to differ considerably from other smooth muscle cells (Romano et al 2005). In some species, such as cattle and humans, these cells share characteristics with fibroblasts and have therefore been termed myofibroblasts (Böck et al 1972;Wrobel et al 1979;Hees et al 1989;Holstein et al 1996;Maekawa et al 1996). In boars, only cells of the inner peritubular layer are contractile, whereas outer layers consist of fibroblasts (Pinart et al 2001).…”
mentioning
confidence: 99%
“…Epididymis segment differences have also been noted in the bull (Hees et al, 1989), boar (Stoffel et al, 1990), mouse (Suzuki, 1982;Abe et al, 1984), rat, rabbit (Chubb and Desjardins, 1982), and man (Kormano and Reijonen, 1976). Stoffel et al (1990), in a study of the boar, observed differences in the organization of the epididymis capillary networks of the caput, as compared to those of the corpus-cauda segments.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, the microvasculature of the epididymis, and the absorptive and secretive processes of the epididymis epithelium are morphofunctional prerequisites for the capacity of sperm to fertilize. Past studies of the epididymis microvasculature have mostly focused on laboratory mammals (Clavert et al, 1980;Chubb and Desjardins, 1982;Suzuki, 1982;Abe et al, 1984;Markey and Meyer, 1992), large breeding mammals (Hees et al, 1989;Stoffel et al, 1990), and man (Kormano and Reijonen, 1976). However, few of these studies dealt with species exhibiting seasonal sexual activity, and they revealed very little regarding the role that vascular structures play in the regulation of nutrition and hormone exchanges.…”
mentioning
confidence: 99%
“…On the other hand, previous studies have demonstrated that quite a few lymphocytes occasionally penetrate into the RT in the normal rat, cat, goat, boar, and bull [6][7][8][9][10][11] . Moreover, the presence of penetrating lymphocytes inside the TR in the normal state has been reported in the monkey 6) .…”
Section: Introductionmentioning
confidence: 99%